The timing of optimal capital income tax reforms: The role of intangible capital investment - Juan Carlos Conesa; Bego\~na Domínguez (SERIEs - Journal of the Spanish Economic Association, 2019)
This paper studies the role of intangible capital investment in the timing of optimal capital income tax reforms. Within an infinitely lived worker-capitalist model as in Judd (J Public Econ 28:59-83, 1985), we consider two different economies: one in which capitalists devote physical investment, management time and intangible capital investment to build capital; and a second one in which capitalists do not need to devote intangible capital investment. We perform a Pareto-improving Ramsey tax reform and compare the optimal paths of corporate and dividend taxes during the transition with and without intangible capital. Without intangible investment, optimal corporate income taxes are set at 100% for 10~years and then fall to 0%, while optimal dividend taxes are set to 78% initially and follow a steep decline to 37% over 10~years. With intangible investment, optimal corporate income taxes are set to -~20% initially and slowly converge toward zero, while dividend income taxes are set to 61% initially and follow a slow decline to 27% over 50~years.
Keywords: E62; H23; H25; 330; Optimal policy; Capital taxes; Intangible investment